2015
DOI: 10.1016/j.coastaleng.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the hydraulic interactions of hurricane storm surge and rainfall–runoff for the Houston–Galveston region

Abstract: Planning of traditional coastal flood risk management strategies are largely predicated on storm surge protection against extreme hurricanes, i.e. storm surge. However, (1) hurricane storm surge and (2) hurricane rainfall-runoff are not mutually exclusive flood hazards. Little research has emphasized the need for quantifying and characterizing the joint hydraulic processes between hurricane storm surge and rainfall-runoff during real events for enhancing effective flood risk mitigation. In this regard, an impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 15 publications
(19 reference statements)
0
35
0
Order By: Relevance
“…The analysis herein focuses on extreme precipitation as the primary cause of flooding. We do not consider the backwater effects of elevated water levels due to storm surge or relative sea level rise in Galveston Bay on the ability of the system to drain, but previous studies have suggested that this may be an important factor in determining the intensity and extent of coastal flooding (Torres et al 2015, Sebastian et al 2017. In addition, we acknowledge that other anthropogenic factors have contributed to increased flood risk in Houston, specifically urban development, which has led to floodplain encroachment, increased impervious cover, reduced overland and channel roughness, decreased storage capacity (Brody et al 2008(Brody et al , 2011, and resource withdrawal that has led to subsidence of up to 3 m (10 ft) (http://hgsubsidence.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis herein focuses on extreme precipitation as the primary cause of flooding. We do not consider the backwater effects of elevated water levels due to storm surge or relative sea level rise in Galveston Bay on the ability of the system to drain, but previous studies have suggested that this may be an important factor in determining the intensity and extent of coastal flooding (Torres et al 2015, Sebastian et al 2017. In addition, we acknowledge that other anthropogenic factors have contributed to increased flood risk in Houston, specifically urban development, which has led to floodplain encroachment, increased impervious cover, reduced overland and channel roughness, decreased storage capacity (Brody et al 2008(Brody et al , 2011, and resource withdrawal that has led to subsidence of up to 3 m (10 ft) (http://hgsubsidence.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme water levels resulting from a combination of stormtide flooding and riverine flooding are also known as coincident or compound flood events (IPCC, 2014;. For some time the two flooding drivers involved were treated independently in coastal flood risk assessments (Torres et al, 2015), even though joint-probability analysis highlighted significant dependence between extreme rainfall and extreme storm surges Jones, 2004, 2006;Zheng et al, 2013Zheng et al, , 2014. Therefore studies such as those of Jones (2004, 2006) have suggested taking both processes into account for flood risk estimations in coastal areas.…”
Section: Introductionmentioning
confidence: 99%
“…The examples of the hurricanes given above show that the compound flooding can cause significant damage. Recent studies by several researchers [13][14][15][16] have shown the impacts of rainfall-runoff on coastal flooding. Furthermore, Yang et al [17] demonstrated the significant impact combined flooding can have on the timing and spatial location of evacuation orders given during hurricane events.…”
Section: Background and Motivationmentioning
confidence: 99%